Small bowel neuroendocrine tumors: An analysis of clinical presentation, diagnostic workup and surgical approach—A single center retrospective study - Kroepfl, Veronika; Bellotti, Ruben; Gasser, Elisabeth; Esswein, Katharina; Esser, Hannah; Kafka-Ritsch, Reinhold; Öfner, Dietmar; Perathoner, Alexander (Frontiers in Surgery, 2023)
Background: Neurocrine neoplasms (NEN) of the small bowel (SBNEN) are a rare entity and mostly asymptomatic. The aim of this study was to explore trends in the clinical presentation, diagnostic workup, surgical approach and oncological outcome in patients with SBNEN at our surgical department. Materials and Methods: All patients who underwent surgical resection for SBNEN from 2004 to 2020 at our department were enrolled in this single center retrospective study. Results: A total of 32 patients were included in this study. In most cases, the diagnosis was based on incidental findings during endoscopy or radiographic imaging (n = 23; 72%). Twenty cases had a G1 tumor and 12 cases a G2 tumor. The 1-, 3- and 5-year overall survival (OS) were 96%, 86% and 81%, respectively. Patients with a tumor more than 30mm had a significantly lower OS (p = 0.01). For G1 tumors, the estimated disease-free survival (DFS) was 109 months. Again, the DFS was significantly lower when the tumor had more than 30mm in diameter (p = 0.013). Conclusion: Due to the mostly asymptomatic presentation, the diagnostic workup can be difficult. An aggressive approach and a strict follow-up seem to be important for the oncological outcome.